Characterisation of coastal landscape characters for scenic tourism route - Zulkifli, Nabilah Huda; Ibrahim, Putri Haryati; Zakariya, Khalilah (2019)
Pahang and Terengganu are coastal states with abundance of rural tourist attractions. The east-coast region has a mix of distinctive built environments and panoramic natural landscapes that are complemented with rich heritage food and culture that can be enjoyed through drive tourism. However, the landscape features of the east coast region are fragmented by other types of landuse such as industrial areas, commercial areas, and townships. While it is undeniable that most places will go through the process of development and infrastructural improvements as part of their growth, it is important to identify the rural landscape characters and tourism assets to protect and optimise the usage of the resources, and potentials to generate income for the local community. The aim of this study is to identify and characterise the coastal rural landscape characters along the east coast route from Pahang to Terengganu, by examining and categorising the rural characters deemed significant by locals and tourists. Through methods of questionnaire survey and interviews, this study examined one of the oldest roads in Malaysia, which is the E3 route (also known as AH18). The findings revealed that the integration of the rural landscape characters into the coastal tourism route planning can offer a rich tourism experience and a better quality regional destination image. The enhancement and composition of landscape characters with tourism resources signify the cultural landscape of an area, which is essential to the planning of multi-destination tourism route for the east coast region.